Breastfeeding and infant/young child feeding in Nepal - Shah, Sunil (2019)
Background: Under nutrition being a major problem in Nepal, it is necessary to meet the minimum dietary standard which is essential for growth and development of young children, so promotion of infant and young child feeding practices among children is important intervention. Methods: A descriptive, cross sectional study was conducted among mothers of children of Bardia and Kailali districts of under 2 years and data was collected using the pre-tested questionnaire. Results: The study shows 30.3 percent of the mothers initiated breastfeeding within an hour of birth, 47.9 percent gave colostrums, 25.5 percent were practicing exclusive breastfeeding at 6 or more months,60 percent mothers fed anything else as prelacteal feed before breast feeding, 60 percent of mothers started complementary feeding between 3-6 months, 47.9 percent of mothers used anything from a bottle with a nipple yesterday or last night, 74.8 percent of mothers were currently breast feeding their children, 58 percent used iodized salt and 70.05 percent revealed that their child received Vit A within last six months. Conclusions: The present study showed that late initiation of breast feeding and practice of prelacteal feeds among home delivered mothers being high. The frequency of complementary feeding ranged was less and early/late weaning are still widely prevalent, use of bottle feeding is high, use of iodized salt is still low. There is a need to educate the mothers regarding proper infant/child feeding practices.